POLA PEMAHAMAN WANITA HIJAB BERJOGET DI MEDIA SOSIAL PERSEPEKTIF HUKUM ISLAM - Habibah Zulaiha; Windi Ria Sarista; Dermina Dalimunthe (Yayasan Baitul Hikmah al-Zain, 2024)
Swaying or dancing is often done by many women, especially on social media, where Muslim women dance and look very engrossed and proudly include videos of their dancing on their social media and they do this in order to get praise from people who watched it and those who danced, hoping for a like for their dancing video. Even though in Islamic law there are two laws for dancing, namely makruh and haram, it is called makruh because it is caused by a matter that does not cause good and so this thing is said to be makruh. And what is said to be haram is when a movement occurs that causes immorality, for example, doing erotic movements and one's private parts are exposed so that this can give rise to lust.